Electroweak measurements in electron positron collisions at W-boson-pair energies at LEP - Schael, S; Barate, R; Bruneliere, R; Buskulic, D; De Bonis, L; Decamp, D; Ghez, P; Goy, C; Jezequel, S; Lees, J; Lucotte, A; Martin, F; et al. (2013)
Electroweak measurements performed with data taken at the electron-positron collider LEP at CERN from 1995 to 2000 are reported. The combined data set considered in this report corresponds to a total luminosity of about 3fb-1 collected by the four LEP experiments ALEPH, DELPHI, L3 and OPAL, at centre-of-mass energies ranging from 130GeV to 209GeV. Combining the published results of the four LEP experiments, the measurements include total and differential cross-sections in photon-pair, fermion-pair and four-fermion production, the latter resulting from both double-resonant W W and Z Z production as well as singly resonant production. Total and differential cross-sections are measured precisely, providing a stringent test of the Standard Model at centre-of-mass energies never explored before in electron-positron collisions. Final-state interaction effects in four-fermion production, such as those arising from colour reconnection and Bose-Einstein correlations between the two W decay systems arising in W W production, are searched for and upper limits on the strength of possible effects are obtained. The data are used to determine fundamental properties of the W boson and the electroweak theory. Among others, the mass and width of the W boson, mW and ΓW, the branching fraction of W decays to hadrons, B (W → had), and the trilinear gauge-boson self-couplings g1 Z, κγ and λγ are determined to be: mW=80.376±0.033GeV ΓW=2.195±0.083GeV B(W→had)=67.41±0.27% g1 Z=0.9840+0.018 -0.020 κγ=0.982±0.042λγ=-0.022±0.019. © 2013 Elsevier B.V.